2017
DOI: 10.1016/j.tox.2017.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Predicting drug-induced liver injury: The importance of data curation

Abstract: Drug-induced liver injury (DILI) is a major issue for both patients and pharmaceutical industry due to insufficient means of prevention/prediction. In the current work we present a 2-class classification model for DILI, generated with Random Forest and 2D molecular descriptors on a dataset of 966 compounds. In addition, predicted transporter inhibition profiles were also included into the models. The initially compiled dataset of 1773 compounds was reduced via a 2-step approach to 966 compounds, resulting in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(78 citation statements)
references
References 74 publications
3
75
0
Order By: Relevance
“…Drug-induced liver injury (DILI) is the term used for liver damage caused by drugs, herbal agents or nutritional supplements. 1 DILI has become one of the most important concerns in modern drug development as it is a leading cause of drugs failing clinical trials and being withdrawn from the market. 2 DILI is also an important issue in traditional Chinese medicines (TCMs), [3][4][5] which have been widely used in the ethnic Chinese population and have become increasingly popular in Western society.…”
Section: Introductionmentioning
confidence: 99%
“…Drug-induced liver injury (DILI) is the term used for liver damage caused by drugs, herbal agents or nutritional supplements. 1 DILI has become one of the most important concerns in modern drug development as it is a leading cause of drugs failing clinical trials and being withdrawn from the market. 2 DILI is also an important issue in traditional Chinese medicines (TCMs), [3][4][5] which have been widely used in the ethnic Chinese population and have become increasingly popular in Western society.…”
Section: Introductionmentioning
confidence: 99%
“…1, S1, and S2) despite showing similar chemical similarity distribution to the training set as seen for the external test set (Fig. 2b) (9) which demonstrated that careful data curation can lead to improved performance, it should be noted that the sample size of the external test set and in particular the FDA validation set (49 compounds) were small. This makes it difficult to accurately evaluate model performance and accordingly also to confidently compare models (Fig.…”
Section: Discussionmentioning
confidence: 66%
“…Major challenges associated with the prediction of DILI using in vitro approaches lie in identifying relevant assays (5) and extrapolating from assay concentrations to in vivo blood concentrations associated with a hepatotoxic risk (6). Numerous in silico models have been generated based on molecular structure (7)(8)(9)(10)(11)(12) and in vitro readouts, such as bioactivity (13) and gene expression (14) in cell culture, which are able to predict DILI better than random, but with a…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data mining approaches to investigate underlying relationships or data extraction for the creation of in silico tools are only feasible if individual terms (e.g. specific histologies of liver findings) can be found and attributed to the harmonized expression .…”
Section: The Necessity Of Harmonized Data Ontologiesmentioning
confidence: 99%